Strategi Pembentukan Karakter Siswa Melalui Pembelajaran Humanis - Martsa Aliya Grimalda; Abdul Rahman; Yosafat Hermawan (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
The nation's moral decline can be seen in the increasing number of juvenile delinquency cases because human values have not been appropriately applied. The government and the people of Indonesia are trying to implement character-building in preparing for the demands of life in the future. Bengawan Solo Natural School, as an educational institution, comes with a humanist learning concept. This study aims to analyze the strategy of forming students' character through humanist learning, inculcating religious character values, and supporting and inhibiting factors at Bengawan Alam Elementary School Solo. The research design used is qualitative descriptive. They are collecting data by interview, observation, and documentation. The results of this study indicate that students' character-building strategies are carried out in several ways or methods, namely practice in the field, habituation, role models, and good close relationships. Through humanistic learning, the facilitator tries to understand the uniqueness of students by the thinking of Emile Durkheim that a person's characteristics indicate the difference or uniqueness of a person's behavior with others. In shaping one's character, developing a personality with creativity and uniqueness is necessary from an early age. The process of inculcating religious values includes the values of discipline, honesty, and independence. The influencing factors include the role of parents, positive habits, the persistence of facilitators, lack of parental cooperation, low enthusiasm for learning from students and facilitators, and responses from residents. The researcher suggests that the cooperation of parents, students, facilitators, and residents is maintained to sustain moral learning.